Re-Desain Ruang Serbaguna dan Restoran Hotel Santika Icon di Gresik - Madeleine Christie Liady; Hedy Constancia Indrani; Poppy Firtatwentyna Nilasari (Intra, 2019)
The city of Gresik is one of the cities that has many local cultures but as time goes by these cultures have begun to disappear until the present generation does not recognize the Gresik culture, visitors and the people of Gresik itself. The hotel is one of the fastest growing commercial buildings in this era. In 2019, the Icon Land property group built several commercial buildings, one of which was a hotel. Commercial buildings are a very good place to introduce new things to visitors. By looking at the problems that exist in Gresik and the potential that exists in commercial buildings, the authors want to design the interior of the Multipurpose Room and hotel restaurant with the concept of a local city, namely the city of Gresik. There has never been a hotel with an interior concept with the culture of the local city. This design aims to introduce the culture of Gresik City to the local community and other urban communities. The culture taken will be applied to the design of the space-forming elements and spatial elements in the Multipurpose Room and hotel restaurant.